Relatório de estágio: a tradução técnica na Word-way: o caso da indústria mecânica - Antunes, Maria Alexandra Barros (2021)
Nowadays, it is possible to understand the importance attributed to the availability of technical information in several languages, mainly by multinational companies, due to the increasing globalization and internationalization. Hence, the technical area ends up being one of the areas that produces most job offers in the translation sector. Technical translation is an area of translation with the purpose to communicate and inform its target audience about technical information and procedures. Therefore, the technical translator must seek to convey the information contained in the original texts clearly and appropriately, in order to achieve effective communication with the target audience. As such, the technical translator cannot only be a translator in the classical sense of the word, as the translator must master other spheres of expertise and be skilled in the use of computer-aided translation tools. Consequently, the competencies of a technical translator do not only focus on the proficiency in a foreign language, but must also fulfil several other requirements and be equipped with different skills. Therefore, firstly, this internship report presents a theoretical context that explores the role and applicability of technical translation in the translation process, giving more relevance to the mechanical industry area. It also discusses the role of computer-aided tools in technical translation. In a second stage, an overview of the whole internship is made, not only of the host company, but also of the tasks performed and the difficulties encountered. In the end, the conclusions about the internship and the work done are pointed out.